Forecasting the dynamics of the model of cold bosonic atoms in a zig-zag optical lattice by symbolic computation - Yue, Xiao-Guang; Shen, Yijuan; Kaplan, Melike; Kaabar, Mohammed K. A.; Yang, Hongmei (World Scientific Pub Co Pte Ltd, 2023)
The work aims to explore the exponential rational function technique and the generalized Kudryashov procedure to investigate one of the most important equations which is the equation of cold bosonic atoms in a zig-zag optical lattice. The considered equation is reduced to a supreme equation by using the continuum approximation which describes the soliton’s dynamics with the implication pulse variables. The adopted techniques are accurate, simple, straightforward, and succinct to compute.